Online colloidal particle monitoring for controlled coagulation pretreatment to lower microfiltration membrane fouling at a potable water reuse facility. (15th June 2022) - Safaee, Helia; Bracewell, Alan; Safarik, Jana; Plumlee, Megan H.; Rajagopalan, Ganesh
Highlights: Colloidal particles in membrane feed monitored using a light scattering technology. Colloidal particle levels in the membrane feed water followed a diurnal pattern. Correlation developed between colloidal particle level and optimum coagulant dose. Real time "targeted" coagulant release reduced 80 to 96% membrane fouling. This technique lowered irreversible fouling with no coagulant leakage in filtrate. Abstract: Fouling of microfiltration (MF)) membranes during water/wastewater treatment is predominantly caused by colloidal particles (size <1 µm) in the feed water. Until recently no online technology was available to directly measure the occurrence of colloidal particles in these waters. This study evaluated the viability of a novel online light scattering technology (Nanoparticle Tracking Analysis) to continuously monitor colloidal particles in the membrane feed water (a secondary-treated wastewater) for targeted removal by injecting coagulant at a dosage proportional to the measured concentration of colloidal particles. A diurnal variation was observed in the colloidal particle concentration in the feed water with the lowest concentration occurring at approximately 6 am and the highest concentration occurring after mid-day. The peak colloidal particle concentrations were 4 to 6 times higher than the lowest concentrations measured on the same day. Bench-scale studies were performed to develop a relationship between colloidal particle concentration and the optimum coagulant dosage required for their removal. Subsequently, a pilot-scale study was performed using two MF pilot units operated in parallel, one receiving targeted coagulant dosing and the other with no coagulant dosing, to demonstrate the effectiveness of targeted coagulant dosing in preventing membrane fouling. The pilot unit that received targeted coagulant dose experienced only 4 to 20% of the transmembrane pressure increase of the increase experienced by the pilot unit that received no coagulant. Evaluation of fouling resistance indicated that targeted coagulation improved flux by predominantly lowering the irreversible fouling. The filtrate water quality measured by colloidal particle concentration, chemical oxygen demand (COD), and turbidity were very similar for the two pilot units. This suggests that although the efficiency of particle and organic materials removal does not change with coagulant addition, the particles filtered by the membrane in the control unit contributed to membrane irreversible fouling, while in the coagulant-treated unit, the coagulated colloidal particles were removed away from the membrane into the backwash stream during the frequent backwash/air scour procedures. Graphical abstract: Image, graphical abstract